2006
DOI: 10.1111/j.1399-5618.2006.00293.x
|View full text |Cite
|
Sign up to set email alerts
|

Comorbidity of attention deficit hyperactivity disorder in juvenile bipolar disorder

Abstract: The rates of comorbid DBD in juvenile bipolar disorder are low. The study does not support a definite relationship between ADHD and juvenile bipolar disorder. Higher rates reported previously may be due to differing methods of subject ascertainment. Samples recruited from community and general psychiatric settings may help to clarify the relationship between bipolar disorder and ADHD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2007
2007
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(15 citation statements)
references
References 34 publications
2
13
0
Order By: Relevance
“…Comorbidity of ADHD and BPD is more likely the earlier the onset of BPD. However, recent studies suggest that the frequency of ADHD in children with juvenile BPD may be lower than previously thought (Jaideep et al, 2006) and their subective self-report of difficulties in attentional/problem solving ability in BPD may not be supported by their performance on objective measures (Robertson, Kutcher, & Lagace, 2003). The problems with sustained attention, working memory, and processing speed in BPD remain present even after after controlling for comorbid ADHD (Doyle, Wilens et al, 2005).…”
Section: Psychiatric Disordermentioning
confidence: 83%
See 1 more Smart Citation
“…Comorbidity of ADHD and BPD is more likely the earlier the onset of BPD. However, recent studies suggest that the frequency of ADHD in children with juvenile BPD may be lower than previously thought (Jaideep et al, 2006) and their subective self-report of difficulties in attentional/problem solving ability in BPD may not be supported by their performance on objective measures (Robertson, Kutcher, & Lagace, 2003). The problems with sustained attention, working memory, and processing speed in BPD remain present even after after controlling for comorbid ADHD (Doyle, Wilens et al, 2005).…”
Section: Psychiatric Disordermentioning
confidence: 83%
“…It has been estimated that approximately 59-87% of children and adolescents with ADHD may have at least one comorbid disorder McGough et al, 2005), and as many as 20% may have three or more comorbid disorders (Rowland et al, 2002). Many of the comorbid conditions present with several core symptoms of ADHD, including bipolar disorder (Biederman, Faraone, Mick, Wozniak et al, 1996;Biederman, Monuteaux, Kendrick, Klein, & Faraone, 2005;Jaideep, Reddy, & Srinath, 2006;Wozniak et al, 2004), anxiety disorder (March et al, 2000;Newcorn et al, 2001), mood disorder (Schmidt, Stark, Carlson, & Anthony, 1998;Wozniak et al, 2004), and childhood abuse/neglect (Glod & Teicher, 1996). Psychiatric comorbidities that involve externalizing disorder with an aggressive component, such as ODD (35.2%, 95% CI 27.2, 43.8) or CD (25.7%, 95% CI: 12.8, 41.3) tend to occur more frequently than those that involve internalizing disorders, such as anxiety (25.8%, 95% CI: 17.6, 35.3) or depressive/mood disorder (18.2%, 95% CI: 11.1, 26.6) (Barkley, Anastopoulos, Guevremont, & Fletcher, 1991;Bird, Gould, & Staghezza, 1993;MTA, 1999a;Shekim et al, 1985).…”
Section: Psychiatric Disordermentioning
confidence: 99%
“…Clinical studies have found rates of BPD ranging from 8.2 to 23% in youths who have ADHD (Wozniak et al 1995;Butler et al 1995;Biederman et al 1996;. Regarding the rate of ADHD in clinic referred subjects with BPD, rates vary widely across samples, from 4 to 98% (Kowatch et al 2005;Birmaher et al 2006;Jaideep et al 2006). Setting, participants age, age of onset of BPD, referral source and ascertainment bias affect these rates.…”
Section: Introductionmentioning
confidence: 94%
“…Each of these comorbid disorders contribute to more coping difficulties . However, putative relationships between adolescent attention-deficit disorder and later onset of bipolar disorder appear to be questionable (Jaideep, Janardhan Reddy, & Srinath, 2006). Higher rates (19.4%) of bipolar disorder are found in patients with borderline personality disorder than among patients with other personality disorders (Gunderson et al, 2006), although this does not appear to be related to outcome.…”
mentioning
confidence: 99%